Theater as an ally of basic education (Research, Society and Development, 2020)
This analysis article, has as its initial premise, the legal guidelines of Basic Education in Brazil, and has as a problem question, what place does the theater occupy in the educational process? In order to answer it, we outline the general objective of demonstrating the importance of theater in the teaching and learning process of students. It is emphasized that the study is bibliographic, explanatory and qualitative, and that the theoretical framework consulted provided subsidies to meet objectives as well as answer the issue of the initial problem. Thus, the results were: the theater represents an educational pedagogical achievement that is opposed to the traditional model of teaching, and occupies a prominent place, since it provides students with union, socialization of ideas and above all learning development in a playful way. . Moreover, it also leads to self-knowledge which implies knowing the other. Thus, the place that theater occupies in education is of real protagonism.